PANORAMA OF INNOVATION IN BRAZILIAN SMALL BUSINESSES - Adriana Dantas Gonçalves (International Journal of Innovation, 2017)
The Local Innovation Agents - LIA (Agentes Locais de Inovação - ALI) Program of the Brazilian Micro and Small Business Support Service (SEBRAE) has monitored over 150,000 small businesses throughout Brazil over the last few years. Within this setting, this article aims to demonstrate the panorama of innovation and management of Brazilian micro and small businesses (MSBs) that were in the initial phase of the LIA program. The analysis of the thirteen dimensions of the Innovation Radar (IR) and the eight dimensions of the Excellence Management Model -EMM (Modelo de Excelência em Gestão - MEG) was performed in a sample of 27,422 small businesses from all over Brazil. Regarding innovation results, four dimensions stand out: Brand, Platform, Offer, and Client Relationship. Besides, the results of the EMM show that Brazilian MSBs still need to improve their management.